2017
DOI: 10.1007/s00408-017-0034-1
|View full text |Cite
|
Sign up to set email alerts
|

Six-Minute Walk Test as a Predictor of Diagnosis, Disease Severity, and Clinical Outcomes in Scleroderma-Associated Pulmonary Hypertension: The DIBOSA Study

Abstract: DIBOSA score is a sensitive tool for the prediction of SSc-PH. The DIBOSA score is a direct predictor of mortality in SSc-PH and strongly correlates with pulmonary pressures. 6MWT can be used to predict clinical outcomes in SSc-PH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…This suggests that the 6MWD still provides useful prognostic information, consistent with the meta-analysis by LEFÈVRE et al [4]. Another recent study by GADRE et al [36] derived a clinical score including the 6MWD, Borg dyspnoea score and oxygen saturation during the walk test, which was associated with haemodynamic severity and survival in SSc-PAH. Interestingly, while baseline 6MWD independently predicted long-term outcomes, haemodynamics and NYHA-FC at baseline did not.…”
Section: Discussionsupporting
confidence: 71%
“…This suggests that the 6MWD still provides useful prognostic information, consistent with the meta-analysis by LEFÈVRE et al [4]. Another recent study by GADRE et al [36] derived a clinical score including the 6MWD, Borg dyspnoea score and oxygen saturation during the walk test, which was associated with haemodynamic severity and survival in SSc-PAH. Interestingly, while baseline 6MWD independently predicted long-term outcomes, haemodynamics and NYHA-FC at baseline did not.…”
Section: Discussionsupporting
confidence: 71%
“…In CTD-PAH, the most investigated underlying disease is SSc. Cohort studies and meta-analyses reported that the parameters classically associated with the severity of IPAH, including 6MWD, mPAP, cardiac index, and RAP, were also prognostic factors in SSc-PAH [22][23][24][25]. For pSS-PAH, however, it is still difficult to identify the patients who may benefit from the treatment more than others due to a paucity of data.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a combination of features obtained during the 6MWT, ie, distance walked, degree of oxygenation and Borg dyspnea index was found useful in identifying patients who need further cardiopulmonary evaluation. 44 Compared with echocardiography, cardiac MRI (CMR) may provide information on the underpinnings of cardiac involvement in patients with SSc, including inflammatory, microvascular and fibrotic mechanisms. 45 Furthermore, CMR provides a more comprehensive assessment of the right ventricular function.…”
Section: Screening For Pulmonary Hypertension In Systemic Sclerosismentioning
confidence: 99%